Pengaruh Keterlambatan Kerja Terhadap Kinerja Waktu Pelaksanaan Proyek Perumahan Griya Amerta Residence - Vajrinanda Aprisaldi Sanduan; M. Natsir Abduh; Savitri Prasandi Mulyani (Program Studi Teknik Sipil Universitas Bosowa, 2026)
Construction projects cannot be separated from obstacles that can cause delays in the work of ongoing construction projects. That obstacle is a factor in the delay in completing the project, so that the project does not run according to the original plan, in this case the Griya Amerta Residence housing project. This study aims to analyze whether there is an effect of delay on the performance of implementation time in the Griya Amerta Residence housing project. This type of research uses an approach method with numerical data that begins with a survey and is analyzed by multiple linear regression analysis operated by the SPSS program. Multiple linear regression analysis is used to find the relationship pattern between bound variables and free variables. Based on the results obtained in the regression model with the output value of sig. 0.000 which means less than 0.05, it can be stated that the labor, material, and financial variables simultaneously affect the performance variable of the implementation time (Y). The factor that has a dominant influence on the performance of the implementation time is the material variable (X2) with a sig. 0.001 and financial variable (X3) with a value of sig. 0.000. which means that both variables have a value of sig. which is less than 0.05, then it can be concluded that these two variables have a significant effect on the performance of implementation time (Y).